Effect of Ionic Liquids on Epoxy Coating - Azlan Bin Othman, Azlan (Universiti Teknologi Petronas, 2011)
In the face of great environmental adversities, „green chemistry‟ has immersed increasingly important day by day. Ionic liquids have overwhelming potential to be posited as solvents for industrial applications to be more environmental friendly. Ionic liquids are basically solvents that can be applied for various applications. One of the most popular advantage of ionic liquids over volatile organic compounds (VOCs) as solvents is the low vapour pressure demonstrated by ionic liquids. Epoxy or polyepoxide is a thermosetting polymer formed from reaction between a resin and harderner (curing agent). Nowadays, epoxy coating is applied widely as corrosion preventive application. Storage tanks and pipes in the industry apply epoxy coating to avoid or slowdown corrosion problem in many cases. Epoxy coatings are normally cured in room temperature condition. However in some occasions, several epoxy coatings are cured in the oven at high temperature.